Geothermal heat flux in the Amundsen Sea sector of West Antarctica: New insights from temperature measurements, depth to the bottom of the magnetic source estimation, and thermal modeling. (22nd July 2017) - Dziadek, R.; Gohl, K.; Diehl, A.; Kaul, N.
Abstract: Focused research on the Pine Island and Thwaites glaciers, which drain the West Antarctic Ice Shelf (WAIS) into the Amundsen Sea Embayment (ASE), revealed strong signs of instability in recent decades that result from variety of reasons, such as inflow of warmer ocean currents and reverse bedrock topography, and has been established as the Marine Ice Sheet Instability hypothesis. Geothermal heat flux (GHF) is a poorly constrained parameter in Antarctica and suspected to affect basal conditions of ice sheets, i.e., basal melting and subglacial hydrology. Thermomechanical models demonstrate the influential boundary condition of geothermal heat flux for (paleo) ice sheet stability. Due to a complex tectonic and magmatic history of West Antarctica, the region is suspected to exhibit strong heterogeneous geothermal heat flux variations. We present an approach to investigate ranges of realistic heat fluxes in the ASE by different methods, discuss direct observations, and 3‐D numerical models that incorporate boundary conditions derived from various geophysical studies, including our new Depth to the Bottom of the Magnetic Source (DBMS) estimates. Our in situ temperature measurements at 26 sites in the ASE more than triples the number of direct GHF observations in West Antarctica. We demonstrate by our numerical 3‐D models that GHF spatially varies from 68 up to 110 mW m −2 . Key Points: Elevated geothermal heat flux Spatial variation of geothermal heat flux on small scales